The Effect of Addition of F3O4 and Sintering Temperature on Properties of the Magnetite/Hydroxyapatite Particles Produced through the Coprecipitation Technique. Issue 1 (February 2021) - Fadli, Ahmad; Iskandar, Dion Julio; Pane, Khobar Bahari
Abstract: Nowadays, the composite of magnetite/hydroxyapatite has become one of the main topics in biomedical field especially as drug delivery system. In this paper, the effect of sintering temperature and Fe3 O4 addition on the properties of coprecipitation produced by magnetite/hydroxyapatite composite is investigated. The magnetite was first dispersed into 100 mL aquadest and mixed with 33.7 mmol Ca(NO3 )2 .4H2 O while stiring for 15 minutes. Subsequently, the mixture was reacted with 20 mmol (NH4 )2 HPO4 for 120 minutes at 90ºC. The mixture pH of 11 during process was controlled by adding NH4 OH 25%. The mixture was left to stand for 1 day, washed and then the precipitate was separated from the mixture. The precipitate was dried at 90ºC for 1 day and it ended with sintering for 2 hours. The composite powder was characterized by field emission scanning election microscopy (FESEM), X-ray diffraction (XRD), and vibrating sample magnetometer (VSM). The result showed that increase in the amount of of Fe3 O4 in the composite, it produced the larger crystalline Fe3 O4 size of 15.59 nm, a decrease in crystallinity to 14.22%, and a higher saturation magnetization was 17.2 emu/g. The higher sintering temperature causes an increase in the size of a hydroxyapatite crystal to 22.94 nm, an increase in crystallinity to 22.55%, and a lower saturation magnetization was 4.0 emu/g.